Optimal therapeutic targeting by HDAC inhibition in biopsy-derived treatment-naïve diffuse midline glioma models. Issue 3 (1st November 2020) - Vitanza, Nicholas A; Biery, Matt C; Myers, Carrie; Ferguson, Eric; Zheng, Ye; Girard, Emily J; Przystal, Justyna M; Park, Giulia; Noll, Alyssa; Pakiam, Fiona; Winter, Conrad A; Morris, Shelli M; et al.
Abstract: Background: Diffuse midline gliomas (DMGs), including diffuse intrinsic pontine gliomas (DIPGs), have a dismal prognosis, with less than 2% surviving 5 years postdiagnosis. The majority of DIPGs and all DMGs harbor mutations altering the epigenetic regulatory histone tail (H3 K27M). Investigations addressing DMG epigenetics have identified a few promising drugs, including the HDAC inhibitor (HDACi) panobinostat. Here, we use clinically relevant DMG models to identify and validate other effective HDACi and their biomarkers of response. Methods: HDAC inhibitors were tested across biopsy-derived treatment-naïve in vitro and in vivo DMG models with biologically relevant radiation resistance. RNA sequencing was performed to define and compare drug efficacy and to map predictive biomarkers of response. Results: Quisinostat and romidepsin showed efficacy with low nanomolar half-maximal inhibitory concentration (IC50) values (~50 and ~5 nM, respectively). Comparative transcriptome analyses across quisinostat, romidepsin, and panobinostat showed a greater degree of shared biological effects between quisinostat and panobinostat, and less overlap with romidepsin. However, some transcriptional changes were consistent across all 3 drugs at similar biologically effective doses, such as overexpression of troponin T1 slow skeletal type ( TNNT1 ) and downregulation of collagen type 20 alpha 1 chain ( COL20A1 ), identifying these as potential vulnerabilities or on-target biomarkers in DMG. Quisinostat and romidepsin significantly ( P  < 0.0001) inhibited in vivo tumor growth. Conclusions: Our data highlight the utility of treatment-naïve biopsy-derived models; establishes quisinostat and romidepsin as effective in vivo; illuminates potential mechanisms and/or biomarkers of DMG cell lethality due to HDAC inhibition; and emphasizes the need for brain tumor–penetrant versions of potentially efficacious agents.